ACCOUNTS SYSTEM IN ANIMAL HUSBANDRY FINANCIAL ACCOUNTING IN ROMANIA - Romanescu, Doinita (Economics of Agriculture, 2012)
Agriculture, a continuous source of controversy, uncertainty, specific risks, but viewed as an unique and interesting field, generating interest for the accounting profession, in the sense of importance given to accounting regulations in agriculture, in general, particularly in animal husbandry. It must be attracted attention to Romanian accountant normalizers, that the traditional accounting model does not provide enough information for agriculture in general, animal husbandry in particular. Normalizers accountants, based on the role and importance of the agriculture at the macroeconomic level, reaching the evaluation of the accounting place and role in the society and economic development, must sustain and elaborate new regulations for agriculture accounting, coupled with EU regulations, international and national accounting regulations.